Scaling Analytics Teams in Cross-Functional Environments: A Leadership Blueprint - Vanam, Laxmi (International Journal of Research in Interdisciplinary Studies, 2025)
In today’s data-centric world, the ability to scale analytics teams effectively across cross-functional environments has become a critical factor for business success. This review explores how modern organizations are evolving their leadership models, organizational structures, and cultural frameworks to embed analytics more deeply within diverse departments such as marketing, operations, and finance. Drawing on academic literature, industry case studies, and experimental results, the paper proposes a multi-dimensional leadership blueprint that emphasizes strategic alignment, federated team models, translator roles, and agile methodologies. The findings reveal that organizations prioritizing cross-functional collaboration, leadership engagement, and continuous learning are more likely to achieve successful analytics outcomes at scale. The review concludes with future directions for research and practice, including the integration of AI in analytics governance, the evolution of hybrid leadership roles, and frameworks for building analytics maturity across the enterprise.